2020
DOI: 10.3390/cells9030528
|View full text |Cite
|
Sign up to set email alerts
|

13 Plus 1: A 30-Year Perspective on Microtubule-Based Motility in Dictyostelium

Abstract: Individual gene analyses of microtubule-based motor proteins in Dictyostelium discoideum have provided a rough draft of its machinery for cytoplasmic organization and division. This review collates their activities and looks forward to what is next. A comprehensive approach that considers the collective actions of motors, how they balance rates and directions, and how they integrate with the actin cytoskeleton will be necessary for a complete understanding of cellular dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Thus, a minus-directed motor is highly activated by addition of PA to SLBs. This motor is likely dynein because processive minus-directed kinesins are not found in the genome of Dictyostelium (28). In an earlier report, we have found that Dynein motors cluster into cholesterol-rich microdomains on mature phagosomes, yielding robust motion and frequent minus-directed stalls (9).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a minus-directed motor is highly activated by addition of PA to SLBs. This motor is likely dynein because processive minus-directed kinesins are not found in the genome of Dictyostelium (28). In an earlier report, we have found that Dynein motors cluster into cholesterol-rich microdomains on mature phagosomes, yielding robust motion and frequent minus-directed stalls (9).…”
Section: Resultsmentioning
confidence: 99%
“…During growth, the most significantly downregulated genes were those encoding heat shock proteins ( hspE-1, hspG3 , hspG4, hspG5, hspG6, hspG7, hspG8, hspG12, hspH, hspJ, hspM, dnaja1 ) and genes involved in protein ubiquitination ( ubqG, ubqH, ubqI, ubqJ, DDB_G0285907 ) ( Supplementary Table S1 ). Conversely, the most significantly upregulated genes were those associated with cell cycle progression, including but not limited to, subunits of the anaphase-promoting complex ( anapc3, anapc5, anapc6, anapc7, anapc10 ), and genes involved in mitosis, such as kinesin-related genes ( kif2, kif4, kif10, kif12, kif13 ) ( Castro et al, 2005 ; Nag et al, 2008 ; Tikhonenko et al, 2009 ; Koonce, 2020 ). During starvation, genes related to development ( cotC, cotD, cotE ) were significantly downregulated in cln5 - cells.…”
Section: Resultsmentioning
confidence: 99%
“…DdKif10 is a 1238aa (139 kDa) polypeptide with an amino-terminal motor domain, a central region with two prominent predicted coiled-coil motifs, and a carboxy terminal tail that likely contains cargo-binding regions [17,18]. The motor/neck domain clearly groups to the Kinesin-8 family, with 45% identity over the first 425 residues to the human Kif18A protein.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our previous work suggests that DdKif10 collaborates with DdKif8 (Kinesin-4) to counterbalance dynein pulling activity during interphase in D. discoideum, acting in sum to support the radial MT array [7,18]. Laser cutting of the motile comet-like MT arrays induced by dominant-negative expression of dynein fragments indicates a pushing component that drives MT motility (MT plus-end-directed) [24], and we are unable to produce this distinctive MT behavior in either kinesin null cell background.…”
Section: Discussionmentioning
confidence: 99%